THE ROLE OF BAITUL MAL WAT TAMWIL IN COMMUNITY ECONOMIC EMPOWERMENT: A CASE STUDY OF BMT AL MUTHI'IN YOGYAKARTA - Kitara Alvinita, Aisyah; Amalia, Familia Nur; Fairus, Salma (Nusantara: Journal of Cultural Research, 2025)
This study analyzes the role of Baitul Maal Wat Tamwil (BMT) Al-Muthi’in Yogyakarta in empowering the community's economy, especially for Micro, Small, and Medium Enterprises (MSMEs). Using a descriptive qualitative method, this study found that BMT Al-Muthi’in effectively carries out its intermediary function through various financing programs, personal and educational approaches, and sharia-based MSME training. The "Relaxation and Restart" policy has been proven to help MSMEs overcome economic pressures, despite challenges such as high Non-Performing Financing (NPF) and human resource limitations still exist. Overall, BMT shows financial resilience and plays a role as a strategic partner in increasing the economic capacity of members through an integrated spiritual, social, and economic approach, so it is recommended to strengthen risk management, increase digital literacy, and expand strategic partnerships for sustainable empowerment.in the community economy.